Operational Challenges in Maintenance: A Lean and Agile Approach - Ab Rahim, Mohd Shahrulnizam; Abu Seman, Noor Aslinda (JBS Nexus, 2025)
The Malaysian maintenance industry is vital in sustainable infrastructure and facility management. This paper examines key operational challenges in maintenance and construction, including project delays, workforce shortages, safety risks, miscommunication, and weather disruptions. These inefficiencies can be mitigated by integrating Lean Manufacturing, Agile methodology, Six Sigma, and continuous improvement frameworks. Lean principles and Agile methodology enhance process optimization, reduce delays, and facilitate real-time communication for rapid adjustments. Six Sigma provides data-driven insights to identify sources of operational errors, particularly in safety and communication. Kaizen fosters continuous improvement, addressing emerging issues such as weather disruptions. Research indicates that practitioners and researchers can achieve greater efficiency and cost-effective project outcomes by integrating these methods. Future empirical studies should explore their interrelationships and potential synergy with emerging technologies to further optimize maintenance project success.